Pengaruh Quality of Work Life dan Karakteristik Pekerjaan Terhadap Kinerja dengan Komitmen Organisasional Sebagai Variabel Mediasi pada Dinas Kesehatan Kota Semarang - Sam Budiono; Endang Tjahjaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of quality of work life, job characteristics, quality of work life, and organizational commitment on the performance of Semarang City Health Service employees. This type of research is explanatory research. The results of the quality of work life variable, job characteristics variable, organizational commitment variable, and performance variable have a KMO value which indicates that the criteria for adequacy of this research sample have been met. Based on hypothesis testing and mediation effect testing results obtained: 1). Quality of work life has a positive influence on organizational commitment; 2). Job characteristics have a positive effect on organizational commitment; 3). Quality of work life influences performance; 4). Job characteristics have a positive effect on performance; 5). Organizational commitment has no effect on performance; 6). Organizational commitment is not a variable that mediates the influence of quality of work life on performance; 7). Organizational commitment is a variable that mediates the influence of job characteristics on performance.